Whole body protein turnover in childhood Crohn's disease. Issue 5 (May 1992) - Thomas, A G; Miller, V; Taylor, F; Maycock, P; Scrimgeour, C M; Rennie, M J
Abstract : In order to investigate the effects of treatment on protein metabolism in childhood Crohn's disease whole body protein turnover was measured using a primed constant intravenous infusion of L-[1-13C]leucine and mass spectrometry in 10 children with active disease. Mean rates of protein synthesis and breakdown markedly decreased after treatment with steroids (four) or an elemental diet (six). This suggests that protein synthesis and breakdown are increased during active Crohn's disease in children and are reduced after induction of remission regardless of the type of treatment.